2012
DOI: 10.5171/2012.213910
|View full text |Cite
|
Sign up to set email alerts
|

Does Environmental Performance Really Matter? A Lesson from the Debate of Environmental Disclosure and Firm Performance

Abstract: Prior empirical studies revealed that firms with high environmental performance tend to be profitable, but questions persist about the nature to the relationship. Those questions are referred to: "Does stronger environmental performance really lead to better financial performance?" Alternatively, "Is the observed relationship the outcome of some other underlying firm attributes?" The long debate about the relationship between environmental performance and firm performance in emerging economies still remain inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 53 publications
4
28
0
Order By: Relevance
“…Ferron and colleagues () suggest that enhanced efficiency by saving materials and preventing waste highly affects the cost structure in these countries. Arafat and colleagues (), who state that enhanced CEP affects learning in developing countries, confirm this result. Further, Agan and colleagues () propose that the higher CEP response to CFP in developing countries may also be explained by environmental supplier development.…”
Section: Presentation Of Meta‐analytical Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Ferron and colleagues () suggest that enhanced efficiency by saving materials and preventing waste highly affects the cost structure in these countries. Arafat and colleagues (), who state that enhanced CEP affects learning in developing countries, confirm this result. Further, Agan and colleagues () propose that the higher CEP response to CFP in developing countries may also be explained by environmental supplier development.…”
Section: Presentation Of Meta‐analytical Resultsmentioning
confidence: 68%
“…), learning effects (Arafat et al. ), and environmental supplier development (Agan et al. ) as the most important factors in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…(Appiah, Du, & Boamah, 2017) asserted that the subject of corporate performance has received significant attention from scholars in the various areas of business and strategic management. However, finding useful components of performance measures is a relevant area for research and a major difficulty is defining the appropriate components and showing whether the interpretations that result are reasonable and applicable elsewhere (Arafat, Warokka, & Dewi, 2012). (Wingard, 2001) studied financial performance of environmentally responsible South African listed companies.…”
Section: Historical Perspective Of Environmental Crises In Sub Saharamentioning
confidence: 99%
“…The study discovered that there was negative relationship between environmental regulatory cost and product pricing decision. (Arafat, et. al., 2012) conducted a study on environmental costs and firm performances.…”
Section: Studies In Nigeriamentioning
confidence: 99%
“…The study found that environmental disclosure had significant relationship with ROE and it was also found that environmental disclosure relationship with ROE is insignificant. Arafat et al (2012) examined the relationship between environmental performance, environmental disclosure and firm performance by taking a sample of 33 companies in Indonesia. Environmental disclosure was measured by using PROPER program environmental ratings given by The Ministry of Environment Indonesia, and the financial performance was measured by using variable ROA.…”
Section: Literature Reviewmentioning
confidence: 99%